1988
DOI: 10.1177/00957984880151005
|View full text |Cite
|
Sign up to set email alerts
|

Race and Family Structure Stereotyping: Perceptions of Black and White Nuclear Families and Stepfamilies

Abstract: Previous studies of stereotyping have established that family structure is a cue by which individuals are stereotyped. This study builds on earlier work by adding the variables of race of respondent, family race, and parents' marital status to the analysis and by presenting family units (i.e., stepfamily, nuclear family) rather than family roles (e.g., stepmother, mother) as the trigger to elicit stereotypes. The sample consisted of 308 White and 178 Black students. Race of respondent and family structure of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…There have been very few investigations of the perceptions of stepfamilies as groups, but the limited findings we have indicate that stepfamilies are viewed less positively than most other family forms. For example, Bryant, Coleman, and Ganong (1988) found that stepfamilies were evaluated more negatively than nuclear families. In a more recent study, we asked college students to write what they believed to be culturally stereotyped attributes of nuclear families, single-parent families, and stepfamilies (Ganong & Coleman, 1996).…”
Section: Downloaded By [Stockholm University Library] At 07:43 11 Augmentioning
confidence: 99%
“…There have been very few investigations of the perceptions of stepfamilies as groups, but the limited findings we have indicate that stepfamilies are viewed less positively than most other family forms. For example, Bryant, Coleman, and Ganong (1988) found that stepfamilies were evaluated more negatively than nuclear families. In a more recent study, we asked college students to write what they believed to be culturally stereotyped attributes of nuclear families, single-parent families, and stepfamilies (Ganong & Coleman, 1996).…”
Section: Downloaded By [Stockholm University Library] At 07:43 11 Augmentioning
confidence: 99%